Effect of Dietary Zinc on the Antioxidant Parameters of Juvenile Common Carp (Cyprinus carpio) - Mustafa, Shokri; Harlıoğ, Muzaffer Mustafa; Aksu, Önder; Batool, Zahra (My University, 2024)
Zinc (Zn) is an essential micro mineral needed for the proper growth and immune function of fish. This investigation was designed to examine the antioxidant role of a fortified diet with different Zn levels in the muscle and liver tissues of carp fry. A four-iso-nitrogen (35% crude protein) practical diet was produced that included graded levels of dietary zinc sulphate as a nutritional zinc resource in the fundamental diet supplemented with increased zinc levels (T1, control, 85 mg Zn kg-1, T2 105 mg Zn kg-1, T3, 125 mg Zn kg-1 and T4, 145 mg Zn kg-1). Even though the SOD and CAT analysis results did not show a linear increase in the increasing Zn ratio in the diets, higher values were obtained compared to the control groups. SOD highest values in T3 for the liver (0.713 ± 0.220 U/ml) and T1 for muscle (0.751 ± 0.144 U/ml), CAT values were highest in T2 for the liver (0.849 ± 0.115 nmol/dk/m) and T2 for muscle (1.059 ± 0.148 nmol/dk/m) was obtained. MDA values were completely higher for the muscle than for the control group, and for the liver, a lower value was obtained in the T2 trial group than in the control group (1.671 ± 0.230 µM). The results of the study showed that Zn contributed significantly to the nutrition of carp fish. It can be concluded that the findings of SOD and CAT analysis endorse the positive contributions of using 105 mg Zn in the diets to promote the antioxidant defense of juvenile carp fish.
Keywords: Antioxidant; liver; superoxide dismutase; catalase; muscle